Constituent Year Effects and Performance in Alpine Skiing Junior World Championships - Øyvind Bjerke; Håvard Lorås; Arve Vorland Pedersen (MDPI AG, 2023)
This study examines constituent year effect (CYE) and race performance among junior alpine skiers in the World Championships. In various junior age cohorts competing together, variation in skiing performance can be expected not only due to practice load and experience but also due to inter-individual differences in physical and psychological maturation. Within a one-year cohort, this effect has been referred to as the birth month effect or the relative age effect (RAE). In cohorts with multiple age bands, the effect is termed the constituent year effect (CYE). The CYE works in principle as the RAE but can function as a magnifying lens of the development within a larger multi-year cohort. The results of the current study indicate that CYEs are present among junior alpine skier performance in the junior World Championships. The magnitude of the constituent year effect is greater in speed events (i.e., downhill and super-G) than in technical events (i.e., slalom and giant slalom), and greater among male skiers compared to female skiers. The findings are discussed in relation to previous research on relative age effects more generally and within the sport context specifically.